Fetishistic disavowal and elusive jouissance: The case of the South African higher education decolonization project - Maistry, S.M. (South African Journal of Higher Education, 2019)
In this paper, I argue that attempts at decolonizing higher education as transformative project in an era of a toxic, exponentially strengthening neoliberal performativity agenda, is inherently paradoxical as any new ‘reconstitution’ is bound to still remain ensnared within the neoliberal grand narrative. Such reconstitution will produce new (dis)guises as institutions in their quest to acquiesce, engage a superficiality that might obfuscate ‘authentic’ transformation. Any kind of transformation is more likely to render futile and instantly obsolete the very benchmarks by which we might recognise its manifestation. As such, its cognitive comprehension sustains a perpetual elusiveness, its realisation, an unattainable jouissance, as a positivist predetermination of the precise co-ordinates of decolonization’s outcome is likely to render the transformative project vacuous. The decolonization enterprise and illusions of its comprehensibility is thus a mark of our incomprehensibility. Its absolute apprehension can only be our realisation of its non-apprehensibility. As such, quick-fix, knee-jerk knowledgeability necessarily essentialises complexity, the consequence of which, is degenerative dilutive concoctions in the name of appeasement. True decolonization necessarily self-determines its yardsticks for evaluation, as it is precisely in its fluid (de)colonized outcomes that its ‘neo-colonization’ with all its frailties is revealed. True transformation and decolonization in the Foucauldian sense is only possible through a ‘significant discursive event’, a rupture of unimaginable proportion, a Žižekian ‘self-destructive’ purification. Anything less will simply reinforce colonialism’s normalcy, thereby reducing any ‘emancipatory’ initiative, a farcical ‘fetishistic disavowal’.